TINGKAT PEMAHAMAN SISWA PADA GAMBAR TEKNIK DASAR: STUDI KASUS DI SMK PIRI SLEMAN YOGYAKARTA - Riyadi, Andrian; Zaman, Fajrin Sidiq Muzaffarul; Saputri, Aufaa Riezka; Endrayanti, Fiki Desi Tri (Universitas Tanjungpura, 2025)
Understanding basic technical drawings is an essential competency for vocational high school students in the field of mechanical engineering to support their readiness for industry demands. This study aims to reveal the extent of understanding of basic technical drawings among students of SMK Piri Sleman Yogyakarta. The research employs a descriptive quantitative approach. The study population consists of 26 students from the XI and XII grades of the Mechanical Engineering expertise program. The data collection method used is a test method with question instruments to measure students' understanding of basic technical drawings. The research findings indicate that the average level of student understanding of technical drawings is 80,57, with the highest score being 92,5 and the lowest score being 67,5. The understanding level for grade XI in mechanical engineering is 79,37, while for grade XII, it is 81,60. Students demonstrated the highest understanding in the topic of the function of technical drawings, while the lowest understanding was in geometric construction. Based on these data, it can be concluded that the level of understanding of basic technical drawings among students in the mechanical engineering expertise program is relatively good.